Adsorption characteristics of nano-TiO2 onto zebrafish embryos and its impacts on egg hatching. (July 2016) - Shih, Yu-Jen; Su, Chia-Chi; Chen, Chiu-Wen; Dong, Cheng-Di; Liu, Wen-sheng; Huang, C.P.
Abstract: The characteristics of nanoparticles (NPs) uptake may fundamentally alter physicochemical effects of engineered NPs on aquatic organisms, thereby yielding different ecotoxicology assessment results. The adsorption behavior of nano-TiO2 (P-25) on zebrafish embryos in Holtfreter's medium (pH 7.2, I ∼ 7.2 × 10 −2 M) and the presence of sodium alginate (100 mg/L) as dispersant was investigated. Zebrafish embryos (total 100) were exposed to nano-TiO2 at different concentrations (e.g., 0, 10, 20, 60, 120 mg/L) in batch-mode assay. The adsorption capacity of nano-TiO2 on fish eggs was determined by measuring the Ti concentration on the egg surface using ICP-OES analysis. Results showed that the adsorption capacity increased rapidly in the first hour, and then declined to reach equilibrium in 8 h. The adsorption characteristics was visualized as a three-step process of rapid initial layer formation, followed by break-up of aggregates and finally rearrangement of floc structures; the maximum adsorption capacity was the sum of an inner rigid layers of aggregates of 0.81–0.84 μg-TiO2 /#-egg and an outer softly flocculated layers of 1.01 μg-TiO2 /#-egg. The Gibbs free energy was 543.29–551.26 and 100.75 kJ/mol, respectively, for the inner-layer and the outer-layer aggregates. Adsorption capacity at 0.5–1.0 μg-TiO2 /#-egg promoted egg hatching; but hatching was inhibited at higher adsorption capacity. Results clearly showed that the configuration of TiO2 aggregates could impact the hatching efficiency of zebrafish embryos. Graphical abstract: Highlights: This work describes the adsorption behavior of TiO2 nanoparticles by zebrafish embryos. Maximum capacity is estimated through Langmuir model. TiO2 dose influences the stages of flocculation and aggregation on embryos. Effects of TiO2 conformation on hatching properties are proposed.